Cannabis Use Disorder: A Review (Advancements in Homeopathic Research, 2022)
Background: Cannabis use is rising and becoming  a trending drug among youth. The drug is used in  different forms, leading to intoxication, acute and  long-term consequences. About 2.8% of Indians  aged 10-75 years are current users of any cannabis  product. Withdrawal from the drug use requires  medical intervention and counselling. Objectives: To identify existing evidence in  homoeopathy on drug deaddiction and cannabis use  disorder and to update the physicians on diagnosis,  risk behaviours, treatment and investigations  associated with cannabis use disorder. Methods: A review of existing literature was  conducted through internet sources and the CCRH  headquarters library using keywords i.e. substance  use, substance abuse, marijuana, cannabis abuse,  drug abuse, cannabis use disorder etc. Data from  studies reporting drug abuse to identify the type of  drug use and homoeopathic treatment response in the  withdrawal and long-term management and treatment  of drug dependents was tabulated. Results: Although some studies have been conducted  on drug withdrawal, no studies have been conducted  on cannabis use disorder. More case studies and  research on treatment of cannabis use disorder using  Homoeopathy are needed.  Interpretation: Physicians need to update  themselves on diagnosis, risk behaviours, treatment  and investigations to counter the condition and  contribute to generating evidence-based literature on  the homoeopathic approach for treating cannabis use  disorder.
Keywords: Cannabis; drug use; homoeopathy; psychoactive substances; THC; withdrawal